(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents an exclusive interview with Professor Ida Ayu Wimba Ruspawati, a faculty member of the Dance Programa at the Institut Seni Indonesia (ISI – Denpasar), and legong dancer since childhood. The conversation explores the origins of the legong dance and its stylistic variations across different regions of Bali. The interviewee shares her learning experiences with various masters – such as Ketut Arini and Gusti Agung Susilawati – and in villages like Saba, Peliatan, Bedulu and Tista, amassing a vast and diverse technical repertoire. She also reflects on her role as teacher, dancer, and creator of new choreographies within the tradition of legong.